Implementation of halal principles in a nanotechnology-based drug delivery system: Review of materials, critical issues, and opportunities for development - Rasyida, Azka Azhari (Maliki Interdisciplinary Journal, 2026)
The development of nanotechnology has led to the emergence of various drug delivery systems, including liposomes, lipid nanoparticles (LNPs), nanoemulsions, solid lipid nanoparticles (SLNs), and polymeric nanoparticles, which can improve drug solubility, bioavailability, stability, and therapeutic effectiveness. At the same time, the growing awareness of halal healthcare products among Muslim consumers has increased the need to evaluate the halal aspects of pharmaceutical products, including those based on nanotechnology. This review aims to examine the characteristics of different nanocarriers, identify the critical halal points of their constituent materials, and discuss the challenges and opportunities in the development of halal nanopharmaceuticals. A literature review approach was used by analysing scientific publications related to nanotechnology-based drug delivery systems and halal pharmaceuticals. The findings show that common nanocarrier materials include phospholipids, cholesterol, solid lipids, surfactants, polyethylene glycol (PEG), and various natural and synthetic polymers. Several of these materials may present critical halal concerns due to their animal-derived sources, manufacturing processes, or potential cross-contamination during production. Therefore, the implementation of halal principles in nanopharmaceutical products requires careful consideration of raw material sources, manufacturing processes, traceability, and halal certification. Integrating halal compliance with product quality, safety, and efficacy may support the development of nanotechnology-based drug delivery systems that fulfil the principles of halalan tayyiban.